Re-evaluation of binding properties of recombinant lymphocyte receptors NKR-P1A and CD69 to chemically synthesized glycans and peptides - Rozbeský, Daniel; Krejzová, Jana; Křenek, Karel; Prchal, Jan; Hrabal, Richard; Kožíšek, Milan; Weignerová, Lenka; Fiore, Michele; Dumy, Pascal; Křen, Vladimír; Renaudet, Olivier (International journal of molecular sciences, 2014)
The binding of monosaccharides and short peptides to lymphocyte receptors (human CD69 and rat NKR-P1A) was first reported in 1994 and then in a number of subsequent publications. Based on this observation, numerous potentially high-affinity saccharide ligands have been synthesized over the last two decades in order to utilize their potential in antitumor therapy. Due to significant inconsistencies in their reported binding properties, we decided to re-examine the interaction between multiple ligands and CD69 or NKR-P1A. Using NMR titration and isothermal titration calorimetry we were unable to detect the binding of the tested ligands such as N-acetyl-D-hexosamines and oligopeptides to both receptors, which contradicts the previous observations published in more than twenty papers over the last fifteen years.
Keywords: Protein Binding; Receptors, Immunologic; Recombinant Proteins; Antigens, CD; CD antigeny; receptory imunologické; diferenciační antigeny T-lymfocytů; polysacharidy; Oligopeptides; krysa rodu Rattus; rekombinantní proteiny; lektiny typu C; vazba proteinů; Animals; lidé; Lectins, C-Type; Humans; zvířata; Rats; Polysaccharides; Antigens, Differentiation, T-Lymphocyte; oligopeptidy